Perlindungan Hukum dalam Kualitas Pelayanan Medis terhadap Hak dan Privasi Pasien Rawat Inap (Studi Kasus di Rumah Sakit Umum Daerah Provinsi Papua Barat) - Adi Sutrisno; Arief Budiono (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study aims to analyze legal protection, service quality and patient rights and privacy at the Regional General Hospital of West Papua Province. The research method used is a quantitative approach. The data analysis used is verification analysis using a linear regression analysis approach. The verification method is used to test the relationship between variables. The sample consisted of 97 respondents who were taken using random sampling technique. The results of this study show that the effect of legal protection and service quality on patient rights and privacy, with a focus on the Regional General Hospital of West Papua Province, shows that adequate legal protection, in accordance with Law No. 17 of 2023 and Law No. 27 of 2022, plays an important role in maintaining patient rights, including privacy and confidentiality of medical information. The study found that hospitals that implement high service quality standards tend to increase patient satisfaction, which encourages their active participation in care. It is important for hospitals to consistently implement legal protections and improve service quality to prevent patient rights violations, as well as ensure transparent and quality services, which ultimately contribute to better health outcomes.